The Influence of Stress and Self-efficacy on Adolescent Psychological Well-being - Jasmita, Reni; Yandri, Hengki; Kholidin, Farid Imam; Ahmad, Bukhari; Juliawati, Dosi (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2025)
Excessive anxiety, feeling less cared for by parents, withdrawing from the social environment, and feeling excessive fatigue for no apparent reason. From this, the purpose of this study is to determine whether there is an influence between stress and self-efficacy on psychological well-being, The research method used is descriptive correlation quantitative method. With a sample size of 30 people with the criteria, namely adolescents aged 16 to 18 years. The scale used in this study is the Perceived Stress Questionnaire (PSQ) to measure the extent to which situations in an individual's life can be assessed as a perception of stress, Self-Efficacy Questionnaire (SEQ) to measure the extent of one's self-confidence in dealing with various demanding situations in life, The Psychological Well-being-Post-Traumatic Changes Questionnaire (PWB-PTCQ) to assess perceived changes in psychological well-being after a traumatic event. The research data were analyzed using multiple regression methods by utilizing the Statistical Package for Social Science (SPSS) version 20 program. From the results of hypothesis testing, a significant value was obtained between stress and self-efficacy on psychological well-being, the results obtained were (0.002 <0.05) so it can be said that there is a simultaneous influence between stress and self-efficacy on psychological well-being. Suggestions for further research are to deepen the factors that influence self-efficacy, investigate the relationship between stress and self-efficacy in different contexts, and increase the number of respondents so as to get maximum research results